Determination Of The Zero Point Of Building Construction In Area C Of Kadiri University With Polygon Mapping - Wiwit Mely Yanti Jannah; Zendy Bima Mahardana; Rama Putra Nugraha; Onie Wardani; Miya Setiyo Asih; Dwi Irin Mariana; Dodi Setiawan (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2022)
Area C of Kadiri University is an empty land located west of the campus area. The land is planned to construct buildings C, D, and E as a projected study area. In carrying out infrastructure development, it is necessary to have a mapping framework to coordinate building plans. Determining the zero point of action requires a land survey to determine the strategic position and the need for excavation or fill. The method used is a closed polygon with vertical and horizontal theodolite shooting tools. The results of the field details showed several projections of the building plan column from survey data on the location of the P1 device with coordinates 31900'43" elevation 123.93 MASL to the northern azimuth value, location P2 with coordinates 291035'48" elevation 125.07 MASL to azimuth P1, location P3 with coordinates 302023'58" elevation 124.179 MASL to azimuth P2,  location P4 with coordinates 29040'50" elevation 123.96 MASL to azimuth P3 and location P5 at coordinates 193056'47" elevation 124.48 MASL to azimuth P4. The land measurement survey data can be projected as a reference image of development and a determinant of zero point (beginning) in acting.